2015
DOI: 10.1088/0960-1317/25/3/035013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a simple, low-cost, T-junction droplet generator fabricated through 3D printing

Abstract: Three-dimensional printing has been recently proposed and assessed for continuous flow microfluidic devices. In this paper the focus is on a new application of this rapid and low cost method for microfluidic device prototyping: droplets production through a T-junction generator. The feasibility of this new methodology is assessed by means of an experimental study in which the statistical parameters which characterize the production of droplets are analyzed. Furthermore, this study assesses the validity of prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Standardized needles were available with smaller inner diameters (60 mm) than the printable channel widths of the 3D printed device. [22][23][24][25] The use of standard needles with xed apertures also ensured the repeatability of fabrication. The diameters of the needles can be selected from 60 mm (34 G) to 1.4 mm (14 G).…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Standardized needles were available with smaller inner diameters (60 mm) than the printable channel widths of the 3D printed device. [22][23][24][25] The use of standard needles with xed apertures also ensured the repeatability of fabrication. The diameters of the needles can be selected from 60 mm (34 G) to 1.4 mm (14 G).…”
Section: Experimental Designmentioning
confidence: 99%
“…Finally, it is difficult to alter the conguration of the device aer fabrication in a completely 3D printed device [22][23][24][25] as the channels are xed and there is no modiable component. In our approach, the modication of the assembled device was achieved for the geometry of the channels (with different 3D printed ttings) as well as the dimension of the nozzles (with different standardized needles).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that removal of support material limited the minimum feature size that could be made. A droplet generator was made via PJ printing that could form different sizes of droplets; their theoretical and experimental sizes were compared, and the polydispersity index of the droplets was determined [40]. …”
Section: Printing Internal Fluidic Featuresmentioning
confidence: 99%